When a Shark Is More Than a Shark: A Sociopolitical Problem-Solving Approach to Fisher-Shark Interactions - Iwane, Mia A.; Leong, Kirsten M.; Vaughan, Mehana; Oleson, Kirsten L. L. (Frontiers in Conservation Science, 2021)
Fisheries are often conceptualized through a biophysical lens resulting in management approaches that fail to account for stakeholder conflicts and sociopolitical inequities. Using a fisher engagement approach, this case study examines the sociopolitical dimensions of fisher-shark interactions in pursuit of more complete problem definitions and effective solutions. Through interviews with Hawaiʻi small boat fishers and observations of a community-based shark-tagging project, we examined fisher perspective, socioeconomic landscapes, stakeholder relationships, and power dynamics. We interpreted these data using an adapted framework that mobilizes concepts from conflict theory and problem definition. We discovered that economic cost, sharks as fishing competitors, and factors of fishers’ on-the-water decisions define the fisher-shark interaction problem at the dispute level. Deeper conflicts include fishers’ poor perceptions of management legitimacy, degraded relationships with researchers and managers, threatened fisher identities, and poor enforcement capacity. Together, dispute and deeper conflicts limit the effectiveness of singular approaches (e.g., regulation) to mitigate fisher-shark interactions and necessitate multi-pronged solutions with substance-, process-, and relationships-based components. This case study documented one such multi-pronged strategy employing fisher-researcher knowledge exchange, collaborative research, and means of more transparent communication. This strategy has the potential to affect both dispute- and deeper-level outcomes by advancing collective understanding of sharks and shark-handling tools, fisher behavior, and reducing shark mortality. Thus, a sociopolitical approach to problem-solving may yield greater collective benefits to fisheries stakeholders and sharks, with broader implications for the systemic management of complex human and biophysical ecosystem components.